Chapter 2 Overcoming the Justice Impasse in Syria - Herremans, Brigitte (Taylor & Francis, 2023)
This chapter discusses what transitional justice can be in a non-transitioning context of internationalised civil war, such as Syria since 2011. It argues that the transitional justice paradigm and its toolkit has allowed Syrian and international justice actors to counter the pervasive defeatism about the pursuit of justice for Syrians. Even when the international justice architecture is impaired, justice actors can still develop concrete initiatives to overcome the accountability gap and make a tangible difference for victims. Drawing on reports by NGOs and interviews with individuals involved in the pursuit of accountability and justice, it describes the evolution of the initial transitional justice efforts and examines the intentions of justice actors who embraced the 'toolkit' as a means of closing the accountability gap, achieve recognition, and disrupt violent state practices. The chapter illustrates why justice actors are using the paradigm of transitional justice in cases where the state is not transitional.